Scars of COVID-19: A bibliometric analysis of post-COVID-19 fibrosis - Zhong, Han; Zhou, Yang; Mei, Shu-Ya; Tang, Ri; Feng, Jin-Hua; He, Zheng-Yu; Xu, Qiao-Yi; Xing, Shun-Peng (Frontiers in Public Health, 2022)
Background The coronavirus disease 2019 (COVID-19) becomes a worldwide public health threat. Increasing evidence proves that COVID-19-induced acute injuries could be reversed by a couple of therapies. After that, post-COVID-19 fibrosis (PCF), a sequela of “Long COVID,” earns rapidly emerging concerns. PCF is associated with deteriorative lung function and worse quality of life. But the process of PCF remains speculative. Therefore, we aim to conduct a bibliometric analysis to explore the overall structure, hotspots, and trend topics of PCF. Materials and methods A comprehensive search was performed in the Web of Science core database to collect literature on PCF. Search syntax included COVID-19 relevant terms: “COVID 19,” “COVID-19 Virus Disease,” “COVID-19 Virus Infection,” “Coronavirus Disease-19,” “2019 Novel Coronavirus Disease,” “2019 Novel Coronavirus Infection,” “SARS Coronavirus 2 Infection,” “COVID-19 Pandemic,” “Coronavirus,” “2019-nCoV,” and “SARS-CoV-2”; and fibrosis relevant terms: “Fibrosis,” “Fibroses,” and “Cirrhosis.” Articles in English were included. Totally 1,088 publications were enrolled. Searching results were subsequentially exported and collected for the bibliometric analysis. National, organizational, and individual level data were analyzed and visualized through biblioshiny package in the R, VOSviewer software, the CiteSpace software, and the Graphical Clustering Toolkit (gCLUTO) software, respectively. Results The intrinsic structure and development in the field of PCF were investigated in the present bibliometric analysis. The topmost keywords were “COVID-19” (occurrences, 636) surrounded by “SARS-CoV-2” (occurrences, 242), “coronavirus” (occurrences, 123), “fibrosis” (occurrences, 120), and “pneumonia” (occurrences, 94). The epidemiology, physiopathology, diagnosis, and therapy of PCF were extensively studied. After this, based on dynamic analysis of keywords, hot topics sharply changed from “Wuhan,” “inflammation,” and “cytokine storm” to “quality of life” and “infection” through burst detection; from “acute respiratory syndrome,” “cystic-fibrosis” and “fibrosis” to “infection,” “COVID-19,” “quality-of-life” through thematic evolution; from “enzyme” to “post COVID.” Similarly, co-cited references analysis showed that topics of references with most citations shift from “pulmonary pathology” (cluster 0) to “COVID-19 vaccination” (cluster 6). Additionally, the overview of contributors, impact, and collaboration was revealed. Summarily, the USA stood out as the most prolific, influential, and collaborative country. The Udice French Research University, Imperial College London, Harvard University, and the University of Washington represented the largest volume of publications, citations, H-index, and co-authorships, respectively. Dana Albon was the most productive and cited author with the strongest co-authorship link strength. Journal of Cystic Fibrosis topped the list of prolific and influential journals. Conclusion Outcomes gained from this study assisted professionals in better realizing PCF and would guide future practices. Epidemiology, pathogenesis, and therapeutics were study hotspots in the early phase of PCF research. As the spread of the COVID-19 pandemic and progress in this field, recent attention shifted to the quality of life of patients and post-COVID comorbidities. Nevertheless, COVID-19 relevant infection and vaccination were speculated to be research trends with current and future interest. International cooperation as well as in-depth laboratory experiments were encouraged to promote further explorations in the field of PCF.